Effect of different plant oils on growth performance, fatty acid composition and flesh quality of rainbow trout (Oncorhynchus mykiss). (10th April 2014) - Yildiz, Mustafa; Köse, İrem; Issa, Ghassan; Kahraman, Tolga
Abstract: This experiment intended to assess the effect of sesame (SO), sunflower (SFO) and linseed (LO) oils on growth performance, fatty acid composition of fillet and liver or flesh quality traits of rainbow trout. Fish fed different four iso‐nitrogenous and iso‐lipidic experimental feeds. The control feed contained only fish oil as the primary lipid source. The fillet eicosapentaenoic acid and docosahexaenoic acid levels were the highest in fish fed control feed. In contrast, the liver eicosapentaenoic acid level was the highest in fish fed LO feed. Fish fed SFO feed had the highest level of total n −6 fatty acids in fillet and liver. Fish fed SO feed had the highest level of 18:1 n −9 fatty acid in fillet and liver. During the 12 days refrigerated storage period at 1°C, thiobarbituric acid (TBA) and pH values gradually increased in all dietary groups. However, trimethylamin nitrogen (TMA‐N) values increased in all dietary groups between days 0 and 9 during the storage period. Generally, pH value in fillets of control group was slightly higher than the other fish groups during 12 days refrigerated storage. Nevertheless, the chemical indicators of spoilage, TBA, TMA‐N and pH values were in the limit of acceptability for human consumption. Results of growth performance and chemical tests in the present study showed that sesame, linseed and sunflower oils could be used in feeds for rainbow trout. Moreover, we concluded that further researches should be carried out on the partial replacement of fish oil by sesame oil in rainbow trout nutrition.